That Derrida whom I derided died : poems 2013-2017 - Stead, C. K. (Christian Karlson), 1932- (Auckland University Press, 2018)
"In his eighty-sixth year, C.K. Stead's new collection leads us deep inside the life of the poet. He looks back at his younger self, remembering old loves and cringing at his 'lugubrious rhyming'. He writes most often of those who have gone (Jacques Derrida and Allen Curnow, Peter Porter and Sarah Broom, Colin McCahon and Maurice Shadbolt, Lauris Edmond and Ted Hughes) but also of those still with us (Kevin Ireland and Fleur Adcock, Alan Roddick and Bill Manhire, Michael Frayn and Paula Rego, his family, himself caught naked in the mirror - and dancing). He takes us with him on the poetical life: from Dogshit Park in Budapest to a Zagreb bookshop to the Christchurch Word Festival. The collection includes a series of poems written while the author was poet laureate, including a sequence on World War I in which 'the Ministry' requests poems from our reluctant and sometimes defiant laureate, who responds in the salty voice of Catullus that he has made his own so often before"--Publisher information